Evaluation of Diuretic Activity of Phyllanthus fraternus Web Arial Parts On Albino Rats. - Kalyani, Biradar (International Journal of Pharmaceutical & Biological Archive, 2010)
The Study was designed to evaluate the diuretic activity of Phyllanthus fraternus web (Euphorbiaceae). The 70% methanolic extract of aerial parts of Phyllanthus fraternus were tested by using Wister albino rats. The animals were grouped into 4 groups containing 6 animals in each. All animals were hydrated with normal saline at a dose of 25ml / kg orally 30sec prior to treatment. The group I served as control, group II & III were treated with 100mg/kg and 200mg/kg of 70% methenolic extract respectively. Group IV treated with the standard frusemide 20mg/kg. The volume of urine measured at the end of 6 hrs. The Na+, K+ & Cl- ion concentration in the urine samples were determined. The volume of urine (7.38 ± 0.18 & 9.11 ± 0.14) and urinary Na+, K+ & Cl- ionic concentrations (3.15 ± 0.15 & 6.15 ± 0.24, 2.50 ± 0.10 & 3.57± 0.10) and 5.60 ± 0.13 & 7.39 ± 0.13) were found to rise in test group II and III.